Assessing the swimming and jumping performance of Wyoming fishes with implications for fishway design - Garvey, Chase, author; Myrick, Christopher A., advisor; Kanno, Yoichiro, committee member; Wohl, Ellen, committee member (Colorado State University. Libraries, 2024)
To successfully begin to solve the complex problems facing native fish conservation efforts, we need to seek a deeper understanding of the fish that inhabit the communities that we hope to conserve. With regards to the issue facing the fragmentation of our lotic ecosystems, and the effects that dams and similar structures can have on fish communities, fishways are a common tool used to restore the connectivity of streams by allowing the uninhibited passage of fish. In these experiments we studied the swimming and jumping abilities of Hornyhead Chub (Nocomis biguttatus), Bigmouth Shiner (Notropis dorsalis), Iowa Darter (Etheostoma exile), and Brook Stickleback (Culaea inconstans) in order to provide fisheries managers with criteria for fishway design that will allow the passage of desirable target species, and potentially block the spread of invasive Brook Stickleback. We did this by testing the jumping abilities of each species at various temperatures using artificial waterfalls. After testing groups of fish at various waterfall heights, we used logistic regression to predict the probability of individual fish passage under various conditions. To test the swimming ability of each species, we used swim tunnels to determine the maximum swimming velocity of each species, and estimate their endurance at various swimming velocities. Our results show that a vertical barrier greater than 15 cm will block the upstream movement of nearly all individual Hornyhead Chub. Heights greater than 8.4 cm will block the upstream passage of Bigmouth Shiner, and barriers taller than 6.0 cm will block the upstream passage of Iowa Darter and Brook Stickleback. Given this information, if vertical drops and pool designs were to be incorporated into fishways designed for these species, drops between fishway pools should remain within these thresholds if successful passage is to be achieved. The results of the swimming performance experiments show that each species' swimming abilities are unique relative to their raw maximum swimming abilities and overall endurance. The problem facing engineers and biologists is that many different species that make up these communities are unique, and have characteristics that pose specific challenges or advantages to assisting their movements. Additionally, fisheries scientists must remain cognizant that fishways that allow native fish movement will likely allow the movement of non-target species (including potential invasives) present in the same systems. Managers must balance the trade-offs between restoring native ecosystems and protecting areas that have not been invaded.